2012
DOI: 10.1088/1367-2630/14/8/083006
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating directed networks for better synchronization

Abstract: In this paper, we studied the strategies to enhance synchronization on directed networks by manipulating a fixed number of links. We proposed a centrality-based manipulating (CBM) method, where the node centrality is measured by the well-known PageRank algorithm. Extensive numerical simulation on many modeled networks demonstrated that the CBM method is more effective in facilitating synchronization than the degree-based manipulating method and the random manipulating method for adding or removing links. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…In this case, he verified that optimized networks present homogeneous in-degree and skewed out-degree distributions. Directed networks were also analyzed by Zeng et al [341], where the authors changed only a fixed number of links in order to shorten the convergence time to synchronization on directed networks.…”
Section: Optimization Of Synchronizationmentioning
confidence: 99%
“…In this case, he verified that optimized networks present homogeneous in-degree and skewed out-degree distributions. Directed networks were also analyzed by Zeng et al [341], where the authors changed only a fixed number of links in order to shorten the convergence time to synchronization on directed networks.…”
Section: Optimization Of Synchronizationmentioning
confidence: 99%
“…Motter et al stated that the synchronous state of a power grid has important implications, and showed that the stability of synchronous states in power grids can be enhanced by tuning parameters of the dynamical units [7]. Zeng et al discussed the strategies to enhance synchronizability on directed networks by manipulating a fixed number of links [11]. Tang et al investigated the bifurcation of synchronized regions in delayed dynamical networks with varying nodal parameters, and the influence of coupling delay as well as bifurcation on network synchronizability [12].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, this "less can be more" phenomenon has already been found in many dynamic process. The most well-known example is the synchronization process, in which the synchronizability can be enhanced by removing links [9,10].…”
Section: Introductionmentioning
confidence: 99%